Functions as a service for distributed deep neural network inference over the cloud-to-things continuum - Bueno Calvente, Altair; Rubio-Muñoz, Bartolomé; Martín-Fernández, Cristian; Díaz-Rodríguez, Manuel (Wiley, 2024)
The use of serverless computing has been gaining popularity in recent years as an alternative to traditional Cloud computing. We explore the usability and potential development benefits of three popular open-source serverless platforms in the context of IoT: OpenFaaS, Fission, and OpenWhisk. To address this we discuss our experience developing a serverless and low-latency Distributed Deep Neural Network (DDNN) application. Our findings indicate that these serverless platforms require significant resources to operate and are not ideal for constrained devices. In addition, we archived a 55% improvement compared to Kafka-ML's performance under load, a framework without dynamic scaling support, demonstrating the potential of serverless computing for low-latency applications.
Keywords: Redes de ordenadores; Cloud-to-things continuum; DDNN inference; Fission; Kafka-ML; OpenFaaS; OpenWhisk; Serverless computing